Corporate Criminal Liability for International Core Crimes – A Comparative Analysis of the French and Swiss Regulations - Danielsson,Elsa (2025)
This thesis examines the extent to which the French and Swiss models of corporate criminal liability may inform the development of proposals to extend the jurisdiction of the International Criminal Court (ICC) to encompass legal persons. The study employs a combination of doctrinal and comparative legal methodology, with particular emphasis on the legal models through which criminal liability may be attributed to corporations. The expansion of transnational corporate activity over recent decades has resulted in companies increasingly operating in contexts where they risk involvement in war crimes and crimes against humanity, for example through global supply chains and resource extraction. Despite the transnational nature of such activities, mechanisms of accountability remain predominantly national, which has hindered effective prosecution and generated calls for international solutions. During the Rome Conference in 1998, a proposal was advanced to extend the ICC’s jurisdiction to include legal persons. Although the proposal was ultimately rejected, most States Parties have since introduced forms of corporate criminal liability at the domestic level, and the issue continues to be debated in legal scholarship. France has adopted a model of corporate criminal liability known as responsabilité par ricochet, under which liability is attributed to the corporation through acts committed by its organs or representatives. Switzerland, by contrast, applies a dual model: direct corporate liability based on organisational failure is limited to certain economic offences, while a subsidiary form of liability applies to other offences where organisational deficiencies have prevented the identification of responsible individuals. Both jurisdictions have investigated domestic corporations for alleged involvement in international core crimes arising from transnational operations, notably in the Lafarge and Argor-Heraeus cases, which are analysed in this thesis. The French and Swiss models are compared, after which the technical feasibility of introducing corporate criminal liability into the Rome Statute is assessed. The analysis also addresses objections relating to complementarity and the argument that only natural persons can bear criminal responsibility. The thesis concludes that the prospects for amending the Rome Statute to include legal persons remain limited, primarily due to states’ reluctance to transfer jurisdiction over their own nationals and domestic corporations to the ICC, particularly in a climate of increasing scepticism towards the Court. At the same time, the French and Swiss experiences demonstrate active efforts within national legal systems to address transnational corporate involvement in international core crimes. They also illustrate that hybrid models of attribution are feasible. Ultimately, the choice of model depends on whether corporations are conceived as autonomous bearers of obligations or as legal fictions whose liability must be derived from individual conduct. While organisation-based models may better reflect the structure of modern transnational corporations (TNCs), identification and vicarious liability models remain more widely accepted and are therefore likely to be more politically viable. A central conclusion is that any future framework should allow for parallel liability of corporations and individuals without making one contingent upon the conviction of the other.
Keywords: comparative law; criminal law; public international law